Enhanced melatonin production via aralkylamine N-acetyltransferase overexpression enhances NaCl resistance in transgenic Chlamydomonas reinhardtii (Volvocales, Chlorophyceae). Issue 2 (4th March 2019) - Zhang, Yujing; Gao, Wenying; Lv, Yawei; Bai, Qingqing; Wang, Yingjuan
ABSTRACT: The hormone melatonin (MT) is produced by the pineal gland in animals and can also be found in plants and algae. MT regulates not only sleep, reduces the effects of jet lag, and has anti-aging properties in animals, but also eliminates intracellular reactive oxygen species and promotes vegetative growth in plants. However, research on its biological function in microalgae is still rare. The present study involved the construction of the Chlamydomonas reinhardtii expression vector pDBle-AANAT, which harbours the gene of one of the enzymes of the MT synthesis pathway, aralkylamine N-acetyltransferase ( AANAT ). The AANAT gene was introduced into the genome of the model microalga C. reinhardtii via glass bead transformation. The AANAT transgenic algal strain was identified by resistance screening, culture, and molecular biology methods. Changes in MT content between transformed algal strain and nontransformed algal strains were detected and the antioxidant capacity of the AANAT overexpressing algal strain was analysed under salt stress. The results showed that genetically engineered algae can increase the content of MT in algal cells by overexpressing AANAT . Under salt stress conditions, this can help to improve the enzymatic activity of the antioxidant system of algal cells and reduce membrane damage to counteract the adverse external stress. This enhances the self-protection ability of C. reinhardtii . This study reveals the effects of MT overproduction on the physiological functions of C. reinhardtii . Additionally, the potential functions of MT in the response of C. reinhardtii to stress have been elucidated, thus broadening the functional scope of MT in plants.